2017
DOI: 10.1108/jerer-05-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Energy performance certificates in the Turin real estate market

Abstract: Purpose The purpose of this paper is to assess the impact of the Energy Performance Certificate (EPC) on the Italian real estate market, focusing on old buildings. The contribution of EPC labels to house prices and to market liquidity was measured to analyze different aspects of the selling process. Design/methodology/approach A traditional hedonic model was used to explain the variables of listing price, transaction price, time on the market and bargaining outcome. In addition to EPC labels, the building co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 53 publications
(53 reference statements)
6
48
1
Order By: Relevance
“…The results show a weak (in correspondence to a low level of EPC) or absent influence, even in the model tested with Microzones clusters. In a following study [53], assuming also the literature of the previous work, the impact of the EPC on house prices and to market liquidity is analyzed, considering old buildings. A hedonic model is applied to explain the variables of listing price, transaction price, time on the market and bargaining outcome, considering a sample of about 900 transactions in Turin (period 2011-2014).…”
Section: Analysis Of Supply and Demand Behavioursmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show a weak (in correspondence to a low level of EPC) or absent influence, even in the model tested with Microzones clusters. In a following study [53], assuming also the literature of the previous work, the impact of the EPC on house prices and to market liquidity is analyzed, considering old buildings. A hedonic model is applied to explain the variables of listing price, transaction price, time on the market and bargaining outcome, considering a sample of about 900 transactions in Turin (period 2011-2014).…”
Section: Analysis Of Supply and Demand Behavioursmentioning
confidence: 99%
“…Building construction period distribution, per Microzone, on the left; building EPC level distribution, per Microzone, on the right. (Source:[53]). …”
mentioning
confidence: 99%
“…Furthermore, the model showed that the variables "building quality" and "apartment condition" significantly influenced price values. On the contrary, other variables such as the building typology, the Energy Performance Certificate (EPC) label and the presence of a lift had a low influence on prices and for this reason they were not included in the model [39,42].…”
Section: Spatial Analyses In the 93 Historical Territorial Units (Htus)mentioning
confidence: 99%
“…Furthermore, in Italy house prices are commonly measured in Euro per square meter by buyers, sellers and real estate institutional web sites. We therefore decided to consider the variables' influence on prices measured in Euro per square meter, as outlined in other studies, which analysed the Italian real estate market [35][36][37][38][39]42].…”
Section: The Hedonic Model (Ols)mentioning
confidence: 99%
See 1 more Smart Citation